2010
DOI: 10.1016/j.expneurol.2010.08.024
|View full text |Cite
|
Sign up to set email alerts
|

18F-FECNT: Validation as PET dopamine transporter ligand in parkinsonism

Abstract: The positron emission tomography (PET) tracer 2β-carbomethoxy-3β-(4-chlorophenyl)-8-(2-[18F]-fluoroethyl)-nortropane (18F-FECNT) is a highly specific ligand for dopamine transporter (DAT) that yields higher peak striatum-to-cerebellum ratios and offers more favorable kinetics than most 18F-radiolabeled DAT ligands currently available. The goal of this study is to validate the use of 18F-FECNT as a PET radiotracer to assess the degree of striatal dopamine terminals denervation and midbrain dopaminergic cell los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
60
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 36 publications
12
60
0
Order By: Relevance
“…The solution was then washed with water (30 mL), aqueous saturated NaHCO 3 (30 mL), water again (30 mL), and finally dried over anhydrous Na 2 SO 4 for 12 h followed by evaporation to dryness. The crude product (0.70 g) was purified by crystallization from petroleum ether to afford 0.58 g of compound 6 (1.78 mmol, 89%) as colorless needles and with a purity >99% (HPLC, UV, 220 nm) (2-Fluoroethyl)-4-bromobenzenesulfonate (7). A mixture of 2-fluoroethanol (2.5 g, 39 mmol), anhydrous pyridine (15 mL), and anhydrous THF (30 mL) under an argon atmosphere was cooled to 5°C using an ice/water bath.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solution was then washed with water (30 mL), aqueous saturated NaHCO 3 (30 mL), water again (30 mL), and finally dried over anhydrous Na 2 SO 4 for 12 h followed by evaporation to dryness. The crude product (0.70 g) was purified by crystallization from petroleum ether to afford 0.58 g of compound 6 (1.78 mmol, 89%) as colorless needles and with a purity >99% (HPLC, UV, 220 nm) (2-Fluoroethyl)-4-bromobenzenesulfonate (7). A mixture of 2-fluoroethanol (2.5 g, 39 mmol), anhydrous pyridine (15 mL), and anhydrous THF (30 mL) under an argon atmosphere was cooled to 5°C using an ice/water bath.…”
Section: Resultsmentioning
confidence: 99%
“…1,5,6 Moreover, high degree of testretest reproducibility and extremely high sensitivity of [ 18 F] FECNT for imaging the DAT in PET studies were recently demonstrated. 7 However, the use of this radioligand as a clinical marker for the state of the DAT system is highly dependent on the robustness of the radiochemical process used for its preparation, and this in particular in terms of efficiency and speed. To date, 1,8 [ 18 F]FECNT has been synthesized in a two-step chemical process, involving the preparation of 2-[…”
Section: β-Carbomethoxy-3β-(4-chlorophenyl)-8-(2-[mentioning
confidence: 99%
“…Table 1 describes all primary antibodies and peptides and their concentrations used in this study. The specificity of each of these antibodies has been characterized previously (Dallvechia-Adams et al, 2002;Montana et al, 2004;Nakadate et al, 2006;Masilamoni et al, 2010), and preadsorption of the a1AR antibody with the synthetic a1AR peptide eliminated all labeling (data not shown).…”
Section: Animal Treatment For Immunocytochemistrymentioning
confidence: 92%
“…This study was approved by the Institutional Review Board (IRB) of Asan Medical Center. The diagnostic criteria of DIP were: (1) the presence of parkinsonism, (2) no history of parkinsonism or extrapyramidal disorders before use of the offending drug, and (3) onset of parkinsonism symptoms during use of the offending drug [9]. Data obtained from 20 patients with ischemic changes in the basal ganglia on brain MRI scans were excluded.…”
Section: Subjectsmentioning
confidence: 99%
“…The availability of presynaptic DAT can be evaluated by positron emission tomography (PET) scanning [9,10]. PET is superior to single photon emission tomography (SPECT) in that it has a higher imaging resolution, making it possible to detect subtle changes in the integrity of the presynaptic dopaminergic system.…”
Section: Introductionmentioning
confidence: 99%